The impact of climate change law on the principle of state sovereignty over natural resources - Van Wyk, Sanita (Stellenbosch University, 2017)
This dissertation serves to expand the means within international law by which to address the global interdisciplinary crisis that is climate change. The principle of sovereignty over natural resources is identified as a principle of international law, evolutionary in nature, fundamentally connected to the international legal climate change regime, and able to be impacted by the effects of climate change. The gravity of climate change is illustrated, as is the intricacy and composition of the international legal climate change regime. In the process, a particular shortcoming of the international legal climate change regime is identified, namely the lack of state compliance with climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. The gravity of the effects of climate change warrants the repositioning of any principle of international law that is able to address this shortcoming of the international legal climate change regime and increase the effectiveness of the regime. In this regard it is determined, more specifically, that the gravity of the effects of climate change warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources. Climate change, forming part of the general, growing, global concern for environmental conservation and sustainable development, influences the interpretation and configuration of state rights and state duties in terms of the principle by eliciting an interpretation that restricts state rights and expands state duties. Furthermore, the gravity of the effects of climate change on the well-being of people, warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources as a people-oriented principle as opposed to the conventional state-oriented principle, and ought to be applied with due regard to the rights of people in terms of the principle. The right of people in terms of the principle of sovereignty over natural resources, is identified as the right to economic selfdetermination, which gives effect to the right of people to dispose freely of natural resources. Should this right be promoted in future applications of the principle of sovereignty over natural resources, the right may well be established as constituting a significant basis on which people are able to hold states accountable for climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. In this way, the principle of sovereignty over natural resources, specifically the implementation of the right of people to dispose freely of natural resources in terms of the principle, presents a negative incentive for state compliance with climate commitments and can contribute to addressing the lack of state compliance within the international legal climate change regime. In summary, this dissertation proposes that the grave effects of climate change warrant a repositioning of the principle of sovereignty over natural resources that allows it to constitute a contribution to climate change law and the global fight against climate change.
URI: http://hdl.handle.net/10019.1/101171
Keywords: Climatic changes; Convention on Climate Change 1997; Convention on Climate Change 2015; Environmental law; Kyoto Protocol; Natural resources; Paris Agreement 2015; Self-determination; Sovereignty; United Nations Framework

Oiling the machine: overriding mandatory provisions and public policy in the Hague Principles on Choice of Law in International Commercial Contracts - Dickinson, Andrew (Uniform Law Review, 2017)
Art. 11 of the Principles on Choice of Law in International Commercial Contracts, adopted by the Council of the Hague Conference in March 2015 contains provisions governing the relationship between the system of law1 chosen by the parties under Art. 2(1) (the “chosen law”) and the laws and policies of other systems. It provides as follows: 1. These Principles shall not prevent a court from applying overriding mandatory provisions of the law of the forum which apply irrespective of the law chosen by the parties. 2. The law of the forum determines when a court may or must apply or take into account overriding mandatory provisions of another law. 3. A court may exclude application of a provision of the law chosen by the parties only if and to the extent that the result of such application would be manifestly incompatible with fundamental notions of public policy (ordre public) of the forum. 4. The law of the forum determines when a court may or must apply or take into account the public policy (ordre public) of a State the law of which would be applicable in the absence of a choice of law. 5. These Principles shall not prevent an arbitral tribunal from applying or taking into account public policy (ordre public), or from applying or taking into account overriding mandatory provisions of a law other than the law chosen by the parties, if the arbitral tribunal is required or entitled to do so. In brief summary, therefore, the first and third paragraphs address the relationship between the chosen law and certain laws and policies of the forum, the second paragraph addresses the relationship between the chosen law and certain laws of legal systems other than the forum, the fourth paragraph addresses the relationship between the chosen law and the certain policies of the legal system whose laws would have applied but for the parties’ choice under Art. 2(1) and the fifth paragraph addresses the limits of the application of the chosen law in arbitration proceedings.